(untitled) (Research, Society and Development, 2021)
Temporomandibular Disorder (TMD) encompasses abnormalities in the temporomandibular joint and/or masticatory muscles having headache as the most common symptom. This study aims to compare the prevalence of TMD in headache patients with the average prevalence of TMD in population. The prevalence ratio (PR) was 0,17 (95% CI 0,05-0,52; p<0,01). A major explanation for this phenomenon was underdiagnose of TMD, leading to literature related problems such as abuse of analgesics, greater psychosocial suffering, sleep disorders such insomnia and other comorbidities. Therefore, health professionals treating headache patients should consider TMD as a possible cause of pain to promote more appropriate treatment.